Trends and Patterns in Nature-Based Learning Research in Primary Schools in Indonesia: A Bibliometric Analysis (2015–2025) - Sabriyandi; Muhammad Ragil Kurniawan (International Journal of Learning Reformation in Elementary Education, 2026)
Nature-based learning (NBL) is increasingly promoted in Indonesian elementary education to support contextual learning, sustainability, and 21st-century competencies. However, evidence on how the Indonesian research landscape has evolved remains fragmented. This study conducts a bibliometric mapping of NBL research in Indonesian elementary school contexts from 2015 to 2025. Using Publish or Perish with Google Scholar, 598 records were retrieved, merged, and cleaned in Zotero, and refined into 473 journal articles for analysis in VOSviewer. Publication output increased sharply after 2020 and peaked in 2025, indicating rapid growth of the field. Keyword co-occurrence mapping identified six clusters, dominated by environmental education and ecological literacy, teacher and implementation issues, Indonesia-specific context, and model or program development. Overlay visualization suggests a progression from early conceptual framing to impact-oriented studies, and more recently to integration and program implementation. Density mapping reveals that competency-specific outcomes remain underrepresented, particularly in social collaboration and critical thinking, and that implementation quality signals, such as teacher readiness and assessment alignment, appear less frequently than broad environmental themes. These findings clarify current emphases and gaps, and support future work that combines broader database coverage with systematic review and evaluative designs to measure competency development and curriculum integration for teachers, schools, and policymakers.